Branding and Social Media Marketing to Increase Sales of Banana Chips Products through the use of Whatsapp Business and TikTok - Rina Susanti; Dorothea Ririn Indriastuti (Abdimas Awang Long, 2026)
Bu Umi’s banana chips MSME, located in Pedan Sub-district, Klaten Regency, produces a range of real food-based snacks, including banana chips, breadfruit chips, peyek, and rambak. However, the enterprise continues to face major constraints in marketing, brand identity, and the utilisation of digital technology, which has contributed to relatively stagnant sales performance. This community engagement programme aimed to strengthen product branding and enhance digital marketing capabilities through WhatsApp Business and TikTok. The programme employed a participatory approach involving discussion, training, and direct mentoring with the MSME owner. Key activities included the development of a logo and mascot, packaging refinement, the establishment of WhatsApp Business and TikTok accounts, and the preparation of promotional content. The results indicate that the partner was able to operate WhatsApp Business effectively for customer communication, product catalogue management, and pre-order-based transactions. The partner was also able to utilise TikTok as a promotional platform, leading to increased product visibility. Overall, the programme produced tangible outputs in the form of an online marketing module and strengthened digital marketing competencies, thereby supporting broader market reach and the potential for increased sales.